Conversing with the saints communication in pre-Carolingian hagiography from Auxerre - Egmond, W. S. van 1970- (Utrecht studies in medieval literacy, 2006)
Contents include: 'Constantius' Vita Germani: an Author and His Text', 'Communication in the Vita Germani', 'The Merovingian Sources', and 'Communication in the Merovingian Texts'.